Rumen-protected zinc–methionine dietary inclusion alters dairy cow performances, and oxidative and inflammatory status under long-term environmental heat stress - Danesh Mesgaran, Mohsen; Kargar, Hassan; Janssen, Rieke; Danesh Mesgaran, Sadjad; Ghesmati, Aghil; Vatankhah, Amirmansour (Frontiers in Veterinary Science, 2022)
Dairy cows are susceptible to heat stress due to levels of milk production and feed intake. Dietary supplemental amino acids, particularly rate-limiting amino acids e.g., methionine (Met), may alleviate the potential negative consequences. Zinc (Zn) is beneficial to the immune system and mammary gland development during heat stress. We investigated the impact of a source of rumen-protected Zn-Met complex (Loprotin, Kaesler Nutrition GmbH, Cuxhaven, Germany) in high producing Holstein cows during a long-term environmental heat stress period. Sixty-two multiparous Holstein lactating cows were allocated in a completely randomized design to 1 of 2 dietary treatments as basal diet without (control) or with supplemental Zn-Met complex (RPZM) at 0.131% of diet DM. Cows in the RPZM group had higher energy-corrected milk (46.71 vs. 52.85 ± 1.72 kg/d for control and RPZM group, respectively) as well as milk fat and protein concentration (27.28 vs. 32.80 ± 1.82 and 30.13 vs. 31.03 ± 0.25 g/kg for control and RPZM group, respectively). Zn-Met complex supplemented cows had lower haptoglobin and IL-1B concentration compared with the control (267 vs. 240 ± 10.53 mcg/mL and 76.8 vs. 60.0 ± 3.4 ng/L for control and RPZM group, respectively). RPZM supplementation resulted in better oxidative status, indicated by higher total antioxidant status and lower malondialdehyde concentrations (0.62 vs. 0.68 ± 0.02 mmol/L and 2.01 vs. 1.76 ± 0.15 nmol/L for control and RPZM group, respectively). Overall, results from this study showed that RPZM dietary inclusion could maintain animals’ milk production and milk composition during periods of heat stress. Enhanced performance of animals upon Zn- Met complex supplementation could be partly the result of improved oxidative and immune status.